Vibration Based Fault Analysis of a Centrifugal Cooling Water Pump Using FFT and Pressure Parameters - Muhammad Dicky Agus Prawira; Harus Laksana Guntur (Journal of Social Research, 2026)
Centrifugal pumps in cooling water systems play an important role in maintaining operational stability in the pulp and paper industry. However, vibration often affects these pumps due to hydraulic and mechanical irregularities. This research identifies vibration characteristics in a centrifugal pump using FFT based spectrum analysis. This technique converts time-domain signals into frequency components. The analysis is complemented by suction pressure evaluation to better describe operating conditions. Vibration measurements were carried out using an SKF Vibrometer at six points on the Drive End (DE) and Non-Drive End (NDE) in horizontal, vertical, and axial directions. The results show abnormal conditions at all locations. Vibration velocity reached 10.73 mm/s, which exceeds the ISO 10816 alert (2.80 mm/s) and danger (4.50 mm/s) limits. The suction pressure was recorded at ?0.3 bar, indicating a significant inlet pressure drop. The FFT spectrum reveals a dominant 1× RPM component. This is typically associated with rotor unbalance. The spectrum also shows indications of misalignment or looseness from multi-directional vibration. In addition, broadband energy in the mid- to high-frequency range and a clear spectral "hump" indicate unstable, non-periodic excitation. Mechanical faults may contribute, but several findings stand out. The combination of broadband energy, spectral hump, and low suction pressure strongly suggests cavitation as the dominant fault mechanism. Cavitation occurs when vapor bubbles form and collapse due to insufficient inlet pressure. This process generates a wideband vibration. Integrating FFT-based vibration analysis with pressure data improves fault identification accuracy. This approach provides a reliable framework for centrifugal pump condition monitoring.